Students’ Speaking Skill Based on Video in Elementary School - Iin Kuraesin; Rahman Rahman; Atep Sujana; Wahyu Sopandi; Indra Suhendra (International Conference on Elementary Education, 2020)
The low of students’ speaking skill will impact on the low of students’ ability to express, convey, communicate idea, thought, feeling, and students’ ability to communicate. Students’ speaking skill is very closely related with the students’ listening skill. Through listening to the video students are expected to have speaking skill. This research is aimed at finding out students’ speaking skill based on video in elementary school. Method used in this study is qualitative descriptive method. The subjects of the study as many as 32 of the fourth grade students. The subjects consist of 20 male students and 12 female students in Rancaekek 05 elementary school. The data gathered were analized by applying Likert scale. The result shows that the use of video can improve students’ speaking skill in elementary school and by using video the speaking skill of female students is higher than the speaking skill of male students